2017
DOI: 10.3390/ijerph14010074
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Exposure and Heart Diseases

Abstract: Environmental contamination has exposed humans to various metal agents, including mercury. It has been determined that mercury is not only harmful to the health of vulnerable populations such as pregnant women and children, but is also toxic to ordinary adults in various ways. For many years, mercury was used in a wide variety of human activities. Nowadays, the exposure to this metal from both natural and artificial sources is significantly increasing. Recent studies suggest that chronic exposure, even to low … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
145
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(154 citation statements)
references
References 86 publications
0
145
0
9
Order By: Relevance
“…A recent review suggested that mercury cause neurologic disorders [9], cardiovascular disease [10], and asthma in children [11]. In addition to evidence of mercury effects on various organs, some animal studies have suggested that acute mercury exposure can damage the liver [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review suggested that mercury cause neurologic disorders [9], cardiovascular disease [10], and asthma in children [11]. In addition to evidence of mercury effects on various organs, some animal studies have suggested that acute mercury exposure can damage the liver [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…-An epidemic of neurological disorders (uncontrollable tremor, difficulties in verbal discourse, loss of motor control, sensory disturbances, blindness, mental retardation, coma and even death) -An entire generation of newborns with different pathologies (Hg is teratogenic) and a low IQ Other effects include: gastric, liver, kidney and heart diseases in adults and children [10][11][12][13][14].…”
Section: Mercury Pollution (Hg)mentioning
confidence: 99%
“…According to Giuseppe et. al., 2017 [7], the bioavailability and toxic effects of mercury and its compounds in both fish and human is shown below: Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…A: Oxidation in air and enzymatically in red blood cells and tissues; B: Biomethylation by sulfate-reducing bacteria. (Giuseppe, et. al., 2017) MeHg is a potent neurotoxin that affects the central nervous system causing neurological damage, mental retardation, blindness, deafness, kidney malfunction, and in some cases, death [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation